Unveiling Health Security Patterns in the European Union through a Hybrid Entropy-CoCoSo and K-Means Clustering Framework [version 1; peer review: 2 approved] - Amani A. K. Essayed; Yahya Ali Al-Samawi; Abed Saif Ahmed Alghawli; Adel A. Nasser (F1000Research)
Objectives This study aimed to examine health security (HeS) patterns across European Union (EU) member states to address intra-regional disparities in health security, align with EU-wide policy objectives, and propose evidence-based recommendations for harmonizing preparedness measures while respecting national sovereignty Methods This research employed a hybrid multi-criteria decision-making framework, combining the Entropy Weight Method and Combined Compromise Solution (CoCoSo), to assess and rank EU countries, drawing on six Global Health Security Index indicators. K-means clustering classified countries into three performance tiers: High, Intermediate, and Dangerous. Data from the GHSI (2019, 2021) and the aggregated 2017–2021 period were analyzed to track temporal trends and cross-regional performance disparities. A comparative analysis of HeS priorities with the African and Eastern Mediterranean (EMR) Regions further contextualized the EU's HeS landscape. Results Detection and Reporting, and Rapid Response emerged as the most critical dimensions influencing performance, while Risk Environment and Compliance with Norms showed minimal differentiation. High-performing countries, such as Finland and Germany, demonstrated resilience in surveillance and rapid response, while lower-tier nations, Cyprus, Luxembourg, Malta, and Romania, exhibited systemic vulnerabilities in biosecurity and emergency planning. Post-2019, health system resilience gained prominence, while compliance and risk environment remained neglected. The temporal analysis highlighted post-pandemic shifts in health system disparities. Cross-regional comparisons underscoring context-specific challenges. Conclusion This study highlights the need for targeted investments in surveillance systems, laboratory infrastructure, and crisis preparedness to address specific gaps in different clusters. A metrics-driven framework can reduce regional disparities, promoting equity in preparedness. Policymakers should adopt a collaborative approach to mitigate crises, using high-performing clusters as benchmarks.